Spatial Mobility of Migrant Workers in Beijing, China - Liu, Ran (Springer International Publishing : Imprint: Springer, 2015)
The great migration of farmers leaving rural China to work and live in big cities as 'floaters' has been an on-going debate in China for the past three decades. This book probes into the spatial mobility of migrant workers in Beijing, China, and questions the city 'rights' issues beneath the city-making movement in contemporary China. In revealing and explaining the socio-spatial injustice phenomenon, this volume re-theorizes the 'right to the city' in the Chinese context since Deng Xiaoping's reforms. The policy review, census analysis, and housing survey are conducted to examine the housing rights of migrant workers, who are the least protected and most marginalized displacee groups in Beijing. The comparable studies serve to distinguish the displaced migrants from local displacee groups, and Beijing Municipality's style of governance towards its urban informalities from that in other Third World cities like São Paulo. The reader will gain a better understanding of migrant workers' housing rights in China's globalizing and branding primary cities.   Audience: This book will be of great interest to researchers and policy makers in housing supplies, governance towards urban informalities, human rights and migration control, and housing-related social discontent issues in China today.